Adherence to Prescribed Drugs Among 65–74 Year Old Men Diagnosed with Abdominal Aortic Aneurysm or Peripheral Arterial Disease in a Screening Trial: A VIVA Substudy. (March 2019) - Qvist, Ina; Søgaard, Rikke; Lindholt, Jes S.; Lorentzen, Vibeke; Hallas, Jesper; Frost, Lars
Abstract : Objective: Adherence to antiplatelet and statin therapy in participants diagnosed with abdominal aortic aneurysm (AAA) or peripheral arterial disease (PAD) was examined in a vascular screening trial. Methods: This was a population based cohort study. The study population consisted of 65–74 year old men diagnosed with AAA or PAD in the Viborg Vascular (VIVA) multifaceted screening trial for CVD. Data from the VIVA screening cohort were linked to data from Danish registers from 2007 to 2016. Initiation of antiplatelet and statin treatment was measured within 120 days after screening. Persistence was defined as no treatment gap >100 days between two prescription renewals after screening. A proportion of days covered ≥80% over five years of follow up was used as a categorical cut off for adherence. Results: Among the 18, 748 screened participants, 618 with AAA and 2051 with PAD were identified. Among non-users at baseline, 65% and 62% initiated antiplatelet and statin treatment, 57% and 59% persisted with antiplatelet and statin use, and 60% and 57% were adherent, respectively. Among users at baseline, 73% and 69% had filled an antiplatelet or statin prescription, respectively, within 120 days after screening. Further, 79% and 73% persisted with their antiplatelet and statin treatment, and 89% and 83% were adherent, respectively. Conclusion: In a vascular screening trial, six of every 10 non-users initiated preventive treatment; among these, the adherence rate was 57–60%. Among users at baseline, the five year adherence to antiplatelet and statin treatment exceeded 80%. The effectiveness of screening initiatives might be improved by measures to improve the fulfilment of preventive medication.